Substitusi Ubi Jalar Kuning dan Penambahan Ekstrak Daun â€œGondaâ€ (Spenochlea zeylanica Gaertner) pada Mie Basah - Dewa Made Hardi Juliana; Luh Suriati; I Putu Candra (GEMA AGRO, 2019)
Noodle is a popular food and a favorite of all people. This is stimulated by consumers' need for nutritious, healthy, safe food and practical lifestyle. Noodles that currently exist predominantly contain carbohydrates derived from wheat flour. Substitution and the addition of other components to the noodles will provide added value so that it is more functional. This study aims to determine the effect of yellow sweet potato substitution and the addition of "Gonda" leaf extract on the characteristics of wet noodles. The design used is a Completely Randomized Design (CRD) with two factors and two replications. The first factor is the comparison of wheat flour and yellow sweet potato substitution consisting of (90:10)%, (85:15)%, (80:20)%. The second factor is the addition of "Gonda" leaf extract consisting of: 15%, 20%, 25%. The best results were obtained in the substitution treatment of 10% yellow sweet potato and the addition of "Gonda" 25% leaf extract with a moisture content of 58.88%, ash 0.12%, protein 6.98%, fat 2.91%, carbohydrate 31 , 12% and antioxidant activity 59.60% and subjectively obtained the highest preference value from panelists. Compared with the Indonesian National Standard (SNI) No. 2987-2015, it was found that the wet noodles in this study had fulfilled the requirements except for the slightly higher ash content